ANALISIS RISIKO FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENELITIAN PENUMPUKAN JUMLAH PENUMPANG DI GATE DENGAN METODE FMEA - Wardhani, Larasati Kusuma; Utomo, Eko Budi (STATOR: Jurnal Ilmiah Teknik Mesin, 2023)
Transportation in Indonesia has targets in getting their respective passengers, such as land, sea and air transportation. In air transportation, passengers as consumers or customers, are directly related to the facility service provider, namely the airport. With the increasing number of passengers using facility services at the airport, making the airport also participate in improving performance to provide the best service for its consumers. Waiting room or gate facilities are one of the services presented by the airport to consumers, in this case passengers, to be a waiting room before the departure time of the aircraft arrives. Some of the ideal conditions required by an airport to provide waiting room facility services are a short distance to get to the plane, a waiting room capacity that is directly proportional to the number of passengers and a fairly well allocated gate assignment, adjusting the existing flight schedule every day. This research is to analyze the risk factors that influence the buildup of the number of passengers at the gate which is affected by the time of an airline's on time performance and gate assignment